Grid Resource Discovery Using Web Services - Garg, Ruchi (My University, 2007)
Grids hold the promise to provide global interoperability and interconnectivity involving networks of heterogeneous resources, working in collaboration, to solve problems that cannot be solved using the resources of any single organization. Opportunistic sharing of Internet-connected resources is a low cost method for obtaining access to unprecedented-scale collections of resources. An essential service in any resource-sharing environment is resource discovery: given a description of the resources desired, a resource discovery mechanism returns locations of resources that match the description. Web Services are an XML based set of standards and technologies to integrate software application systems using Internet technology. In practice, there is not much difference between the existing Grid and web infrastructure. The implementation of web based Grid is one of the potential solution to Grid infrastructure based problems. This can be done by sharing Grid services across the Grid infrastructure using the underlying web service as vehicles or transporters of these services. Using web services based resource discovery is a standards based technique for querying resource discovery information which to date, has received surprisingly little analysis as a discovery mechanism for web service based grids. In this thesis, we proposed, designed and implemented Grid resource discovery using web services on a .NET-based Grid computing framework so as to utilize the computing resources of the vast majority of desktop computers i.e. those running variants of the Microsoft Windows operating system. Using this framework, a language independent and platform independent support is provided via a web services interface. Furthermore we can conclude that on the design principles proposed in this thesis work, a complete Grid Middleware can be implemented on the same lines of which only the Resource Discovery portion has been presented here.
M.E. (CSED) Thesis (7th Aug 2007)
Keywords: Grid Computing; Resource Discovery; Web Services; Distributed Computing